Pengaruh Self Esteem terhadap Body Image Remaja Akhir Putri Pengguna Tiktok - Alika Salsabila Rahma Suhardian; Siti Qodariah (Bandung Conference Series: Psychology Science, 2022)
Abstract. Post-pandemic conditions make teenagers more at home and there is an increase in accessing the internet and social media. Currently, Tiktok application is the most popular and in-demand application among teenagers. The city of Bandung is the city with the tiktok in West Java.application tiktok has a lot of content and features that can be played, displayed, and enjoyed by its users. One of the content in tiktok is beauty and fashion content where in this content users are presented and facilitated to contain content regarding their own beauty by appearing on the For Your Page (FYP) tiktok.existence of beauty and fashion that is in great demand among teenagers raises the ideal self so that the term "body goals" among teenagers. Individual social media users who tend to compare themselves with others to get standards like them and are judged to have an impact on self-esteem. Adolescents have thoughts about their physical strengths and weaknesses so that they form a body image. Late teens themselves have the characteristics of self -esteem, and young women are considered more vulnerable to self-esteem. This study aims to see how much influence self-esteem on the body image of late teenage girls using the Tiktok in Bandung. The hypothesis in this study is that there is an influence between self-esteem on the body image of late adolescent girls who use the tiktok in the city of Bandung. Collecting data using the Rosenberg Self-Esteem Scale (RSES) and Multidimesional Body Self Relations Questionnaire-Appereance Scales (MBSRQ-AS). The subjects of this study were 443 late adolescent female respondents who actively use the tiktok who like to view beauty and fashion on FYP tiktok for 1-2 hours per day and live in the city of Bandung. The data obtained shows that there is an influence between self-esteem on the body image of late teenage girls using the Tiktok in Bandung City by 80.7%. Abstrak. Kondisi pasca pandemic membuat remaja lebih banyak dirumah dan adanya peningkatan mengakses internet dan media sosial. Saat ini, Aplikasi Tiktok adalah aplikasi yang terpopuler dan diminati dikalangan remaja. Kota Bandung adalah kota dengan pengguna aplikasi tiktok tertinggi di Jawa Barat. Aplikasi tiktok memiliki banyak konten dan fitur yang bisa di mainkan, ditampilkan, dan dinikmati oleh penggunanya. Salah satu konten di aplikasi tiktok ini adalah konten beauty and fashion dimana pada konten ini pengguna disajikan dan difasilitasi untuk berkonten menyangkut kecantikan diri dengan muncul pada fitur For Your Page (FYP) tiktok. Dengan adanya konten beauty and fashion yang banyak diminati di kalangan remaja memunculkan ideal self sehingga muncul istilah “body goals” di kalangan remaja. Individu pengguna media sosial yang cenderung membandingkan dirinya sendiri dengan orang lain untuk mendapatkan standard seperti mereka dan dinilai berdampak pada self esteem. Remaja memiliki pemikiran mengenai kelebihan dan kekurangan fisik dirinya sehingga membentuk body image. Remaja akhir sendiri memiliki ciri khas self esteem yang tinggi, dan remaja putri dinilai lebih rentan terhadap self esteem. Penelitian ini bertujuan untuk melihat seberapa besar pengaruh self esteem terhadap body image remaja akhir putri pengguna aplikasi tiktok di Kota Bandung. Hipotesis pada penelitian ini adalah terdapat pengaruh antara self esteem terhadap body image remaja akhir putri pengguna aplikasi tiktok di Kota Bandung. Pengumpulan data menggunakan alat ukur Rosenberg Self esteem Scale (RSES) dan Multidimesional Body Self Relations Questionnaire-Appereance Scales (MBSRQ-AS). Subjek penelitian ini sebanyak 443 responden remaja akhir putri yang aktif menggunakan aplikasi tiktok yang suka melihat konten beauty and fashion di FYP tiktok selama 1-2 jam per hari dan tinggal di Kota Bandung. Data yang diperoleh menunjukkan bahwa terdapat pengaruh antara self esteem terhadap body image remaja akhir putri pengguna aplikasi tiktok di Kota Bandung sebesar 80,7%.